Mechanisms of volatile production from amino acid esters by irradiation. (March 2016) - Feng, Xi; Lee, Eun Joo; Nam, Kichang; Jo, Cheorun; Ko, Kyungyuk; Ahn, Dong Uk
Abstract: Proteins and its constituents (amino acids) are known as the major contributors to the off-odor in irradiated meat. However, radiolytic degradation of amino acids occurred not only at side chains but also at amino- and carboxyl-groups of the α-carbon. A model system with amino acid esters was used to elucidate the mechanisms of volatile production at side chains of amino acids by irradiation. The low-molecular weight aldehydes, which contributed to the irradiation off-odor, were mainly from acidic, aliphatic and aliphatic hydroxyl group amino acid esters through the radiolysis of amino acid side chains or Strecker degradation. However, the contribution from non-sulfur amino acids was minor compared with sulfur amino acids. Among the sulfur-containing amino acids, methionine made the greatest contribution to the irradiation off-odor not only through the direct cleavage of the side chain. However, the chemical reactions of sulfur compounds with other compounds produced by irradiation also played significant roles to the off-odor of irradiated meat. Highlights: Irradiation produced new volatiles from amino acid esters. Odor of the irradiated sulfur amino acid esters was similar to irradiated meat. Methionine was the major amino acid responsible for irradiation off-odor in meat. Radiolysis of side chain and Strecker degradation were the major pathways.